PENGARUH CURRENT RATIO, RETURN ON ASSET, ASSET STRUCTURE DAN TOTAL ASSET TURNOVER TERHADAP DEBT TO EQUITY RATIO PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Willy Yusnandar (KRISNA: Kumpulan Riset Akuntansi, 2019)
The use of financial statements requires financial information from the company to analyze the financial performance of the company concerned. Financial ratios can be used as a tool to find out the capital structure of an upcoming company. This research aims to test partially and simultaneously the influence of Current Ratio, Return On Assets, Asset Structure and Total Asset Turnover on Debt to Equity Ratio in Plantation companies listed on the Indonesia Stock Exchange. The research approach used in this research is associative. With the entire population used as a sample of 6 companies for 2009-2015. The data analysis technique used is desktiptif statistics, multiple linear regression tests, hypothesis testing (t-test and F-test) and test the coefficient of determination. The results of this research indicate that partially Current Ratio, Asset Structure and Total Asset Turnover have an effect on Debt to Equity Ratio, while Retrun On Asset does not affect Debt to Equity Ratio. Then the Current Ratio, Return On Asset, Asset Structure and Total Asset Turnover simultaneously influence the Debt to Equity Ratio. Thus financial statement users can consider these ratios as a means of consideration in decision making.